Evaluation and comparison of color change in two commercially shade guides after disinfection - Athira K Nair; Vasantha Vijayaraghavan; Darshana Mundhe; Rohan P Bhave; Bhushan Pol; Madhura Kad Jadhav (Wolters Kluwer Medknow Publications, 2023)
Background: Due to the close proximity to the oral cavity, shade guides are prone to contamination with saliva. Hence, disinfection of shade guides is important to prevent cross infection in clinics. This study has compared and evaluated the color change in VITA shade guide and the WALDENT shade guide after disinfecting with 70% isopropyl alcohol. Objectives: The objective of this study was to compare and evaluate the amount of color change in the VITA shade guide and WALDENT shade guide after disinfecting them with 70% isopropyl alcohol for the simulated time of 6 months and 1 year. Materials and Methods: Four commonly used shade tabs, namely A2, A3.5, B2, and C1 of two shade guides - VITA Classical Shade Guide and Waldent shade guides - were chosen for this study. VITA Easyshade spectrophotometer measured the shade, and the values were recorded in the International Commission on Illumination L*a*b* Scale. Baseline values of 8 shade tabs were obtained followed by surface disinfection using 70% isopropyl alcohol using gauze. The testing process was done to simulate a 6-month period and 1-year period. Results: Unpaired t-test was used for statistical analysis. It was found that shade tabs underwent significant changes in short period of time. Conclusion: Within the limitations of this study, it was found that shade guides undergo significant changes in color when disinfected with 70% isopropyl alcohol during a simulated period of 6 months. Clinical Significance: If shade guides are not periodically evaluated using a control (preferably unused) shade guide, they may have a profound impact on resulting restoration.